Adverse Events: The Need for the United States and Japan to Reform Patient Safety - Rocco Giovanni Motto (Washington University Global Studies Law Review, 2016)
After the Institute of Medicine released a report in 1999 a startling discovery was apparent: between 44,000 and 98,000 hospital patients in the United States died in 1997 as a result of an adverse event. An adverse event is an unfavorable event that is caused by a medical product rather than the primary condition of the patient. In other words, an adverse event describes any harm to a patient as a result of medical care. A later study estimated that between 220,000 and 440,000 hospital patients in the United States suffer from some type of adverse event that contributed to their deaths. Besides in the United States, the occurrences of adverse events are relatively high in every industrialized society throughout the world In analyzing adverse events, this Note explores the advancements and regulations regarding adverse events in the United States and Japan. In doing so, this Note places particular emphasis on the different reporting practices and mechanisms each country has implemented over the years while insisting that the United States government should federally mandate reporting systems. In addition, this Note will explore Japanese initiatives and practices that may help the United States substantially improve patient safety. Furthermore, this Note addresses how the United States may, or may not, benefit from the provisions and practices that are implemented to help increase patient safety in Japan. Ultimately, this Note examines what efforts each country has taken to ensure that adverse events are reduced and patient safety within hospitals increases.
Keywords: Health Law; Regulation; Adverse Event; International Law; Japan